Analisis K3 pada Mesin Milling, Mesin Bubut dan Ruangan Produksi di PT. Z Menggunakan Metode HIRARC - Cristian Saragih, Nofra Alfredo; Fitriani, Risma (Fakultas Teknik Universitas Tulang Bawang, 2024)
Occupational safety and health play a crucial role in maintaining productivity, sustainability, and the reputation of a company. Unsafe or unhealthy working conditions can lead to workplace accidents, injuries, or even fatalities. Additionally, the costs associated with work-related accidents or illnesses can be significant, including medical expenses, workers' compensation, and lost productivity. Therefore, it is important for companies to have an effective occupational safety and health program to protect their employees. One method used to analyze and manage occupational safety and health risks is HIRARC (Hazard Identification, Risk Assessment, and Risk Control). In this report, we will discuss the background of occupational safety and health and explain the steps of HIRARC in identifying, assessing, and controlling occupational safety and health risks in the workplace. The HIRARC method serves as an effort to prevent or minimize workplace accidents and includes a combination of Hazard Identification, followed by Risk Assessment to evaluate potential hazards in milling machines, lathe machines, and production areas, and finally Risk Control to implement measures that can minimize workplace accidents in the working environment. Keywords: HIRARC (Hazard Identification, Risk Assessment, and Risk Control), Occupational safety and health, Production area